Esthetic Dentistry on Twitter: Benefits and Dangers - Nesreen A. Salim; Fahed Jubair; Yazan M. Hassona; Sarah Izriqi; Dana Al-Fuqaha'a (Hindawi Limited, 2021)
Objectives. The demand for esthetic dentistry is growing, and social media constitute the main driving force behind this revolution. Twitter is a leading social media platform; however, there is a lack of research on the pattern of communications and the impact of Twitter on esthetic dentistry. The purpose of this study was to analyze the content of tweets related to esthetic dentistry and to investigate how Twitter has affected the perception of, and demand for, esthetic dentistry. Moreover, it aimed to assess the potential benefits and risks of esthetic dentistry advertising strategies on Twitter as a potential social media platform. Materials and Methods. Using a specialized web scrapping tool made available by the Python programming language, a total of 54,000 public tweets were downloaded from Twitter at real-time by matching specific keywords. The downloaded tweets were manually filtered, and 13,787 tweets were included and categorized into four tweet sets by content. Results. The main categories were tweets regarding specific cosmetic procedure, totaling 56.53% (43.2% for veneers, 13.3% for whitening), advertisements (36.72%), information (5.53%), and general cosmetic dentistry (1.22%). Negative opinions towards veneers and whitening were the most common themes (68.03% and 43.44%). For veneers, illegal use for kids was the most common negative theme (59.7%) and being destructive for whitening (86.3%). Positive opinions counted 6.26% of veneers and 4.3% of whitening tweets. Advertising for whitening products was the second most common between all tweets (16.6%), and advertising for dental practices was the third (14.7%). Presenting facilities/services was the most common marketing strategy for dental practices (49.7%). Twitter was weakly used to circulate educational content (5.5%) and to post reviews (0.75%). Conclusion. Twitter was extensively used to share experiences/opinions towards dental cosmetic interventions. Advertising is another vital use of this platform. However, circulating information was the least common use of this social media. Additionally, tweeters were rarely to post online reviews and specific advices and recommendations regarding esthetic dentistry. Moreover, females tended to participate and tweet more significantly in cosmetic-related topics than males. This platform should be tailored efficiently to target users' priorities and to improve health literacy and self-care. Twitter was weakly used to circulate educational content according to this study and rarely used to share online reviews.